2008
DOI: 10.1111/j.1601-5223.1983.tb00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations and micronuclei in bone marrow cells and peripheral blood lymphocytes in humans exposed to ethylene oxide

Abstract: Twenty‐eight individuals occupationally exposed to ethylene oxide have been compared with 20 controls regarding cytogenetic effects in peripheral blood lymphocytes and in bone marrow cells. The exposure levels of ethylene oxide were estimated and none of the individuals had, during the last 2.5 years, been exposed to workroom air concentrations exceeding 1 ppm. The exposed persons showed significantly increased levels of chromosome aberrations in lymphocytes (about 50% increase of mean) and of micronuclei in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Their technique was essentially the same as that used in the present study. The difference in micronuclei frequencies between smokers and nonsmokers reported by HOGSTEDT et al (1983) was exactly the same as the one I observed (As:2.2x10-3). COUNTRYMAN and HEDDLE (1976) recommend a culture time of 96 h for lymphocyte micronuclei.…”
Section: Micronucleisupporting
confidence: 87%
“…Their technique was essentially the same as that used in the present study. The difference in micronuclei frequencies between smokers and nonsmokers reported by HOGSTEDT et al (1983) was exactly the same as the one I observed (As:2.2x10-3). COUNTRYMAN and HEDDLE (1976) recommend a culture time of 96 h for lymphocyte micronuclei.…”
Section: Micronucleisupporting
confidence: 87%
“…Contrary to the results of MIC-affected smokers, an elevated BNMN and MNL were found in the control group smokers than non-smokers (Table 5). There are only a few studies reported the association between smoking and MN (Hogstedt et al, 1983;Hogstedt, 1984;Sorsa et al, 1988;da Cruz et al, 1994;Di Giorgio et al, 1994;De Boeck et al, 2000). With regard to alcohol consumption, we observed higher MNL only in the control group alcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…These studies additionally provided some insight regarding the choice of cells and their influence on the micronucleus assay. Högstedt et al [22] in their study indicated that MN assay in bone marrow cells was a better indicator than lymphocyte MN. In some of the other studies MN formation was evaluated in exfoliated buccal and nasal cells, in addition to lymphocyte cells.…”
Section: Discussionmentioning
confidence: 98%
“…Högstedt et al [22] investigated the effect of EtO on different cytogenetic parameters in an exposed Swedish population. They studied a group of 28 workers exposed to EtO and 20 control subjects.…”
Section: Epidemiological Evidence Of Mn Formation In Workers Exposed mentioning
confidence: 99%